Rewrite the function f (x) =3(x-1)^2-2 in the form f(x) = ax²+bx+c.

Question

Rewrite the function f (x) =3(x-1)^2-2 in the form f(x) = ax²+bx+c.

in progress 0
Gerda 7 months 2021-07-20T21:40:47+00:00 1 Answers 2 views 0

Answers ( )

    0
    2021-07-20T21:42:30+00:00

    Answer:

    3x^2-6x+1

    Step-by-step explanation:

    According to order of operations, you do exponents before multiplying. So, (x-1)^2=x^2-2x+1, then you multiply it by 3. Lastly, you subtract by 2.

Leave an answer

Browse

Giải phương trình 1 ẩn: x + 2 - 2(x + 1) = -x . Hỏi x = ? ( )